Cutting Efficiency of Instruments with Different Movements: a Comparative Study - Luigi Tocci; Gianluca Plotino; Dina Al-Sudani; Alessio Giansiracusa Rubini; Gianpaolo Sannino; Lucila Piasecki; Ermanno Putortì; Luca Testarelli; Gianluca Gambarini (eJournal of Oral Maxillofacial Research)
Objectives: The aim of the present study was to evaluate the cutting efficiency of two new reciprocating instruments, Twisted File Adaptive and WaveOne Primary.